CHARACTERISTICS OF STREAM OF CONSCIOUSNESS IN THE MODERN ENGLISH NOVELS - Fayzullayeva Dilnoza Ubaydullayevna; Norboyeva Iroda Abdurashitovna (Journal of new century innovations, 2022)
The article presents a comprehensive study of the notion of stream of consciousness in English Literature, its types and learning in modern English novels. Stream of consciousness is a narrative style that tries to capture a character’s thought process in a realistic way. It’s an interior monologue, but it’s also more than that. Because it’s mimicking the non-linear way our brains work, stream-of-consciousness narration includes a lot of free association, looping repetitions, sensory observations, and strange (or even nonexistent) punctuation and syntax—all of which helps us to better understand a character’s psychological state and worldview. As such types of stream of consciousness and its names are discussed in this article particularly.